Short Review on Vaccination and Surveillance on Avian Influenza in Bangladesh: Existing Gaps and Recent Insights (Bangladesh Journal of Infectious Diseases, 2018)
Avian influenza has been considered as a serious threat to veterinary public health of Bangladesh since 2007. The national and international bodies responded so quickly as to control the outbreak at that time. A full scale long time strategic plan and its implementation could protect the country from further outbreak. The dynamic antigenic nature of this virus is an extra concern. Besides, mass vaccination without proper surveillance and use of ineffectiveborder-crossed unauthorized vaccines worsened the situations silently. Recent outbreak of Highly Pathogenic Avian Influenza H5N1 is a matter of topmost national concern. It is time to navigate back to the unresolved issues prioritizing the analysis of existing avian influenza related data and metadata and fortification of surveillance system effectually. LBM (Live Bird Market) sink surveillance might serve the purpose given the feasibility of division wise surveillance system. Only by detecting existing field strain causing infections, master seed can be produced that will eventually result in efficient vaccine. Viral phylodynamics blended with computerized technology now provides prediction of variant protein and their phenotypic characteristics. Also the countries are more united than ever to share the genetic sequence of influenza virus and collaborate more actively.Bangladesh Journal of Infectious Diseases 2017;4(2):48-51